Application of Synchrotron Radiation in Fundamental Research and Clinical Medicine - Chao Xiao; Jinde Zhang; Yang Li; Mingyuan Xie; Dongbai Sun (Biomedicines, 2025)
Synchrotron radiation light sources have been successfully utilized in material science, biomedicine, and other fields due to their high intensity, excellent monochromaticity, coherence, and collimation. In recent years, synchrotron radiation has significantly expedited the advancement of medical applications, particularly through innovations in imaging and radiotherapy. For instance, synchrotron X-ray imaging has enabled high-contrast and spatial–temporal resolution images for early-stage diagnosis of breast cancer and cardiovascular diseases, offering superior diagnostic accuracy compared to conventional methods. Additionally, novel synchrotron radiation-based radiotherapy techniques, such as microbeam therapy and stereotactic radiotherapy, have shown great potential for clinical application by enabling precise tumor targeting while minimizing damage to surrounding healthy tissues. These advancements are projected to redefine imaging diagnostics and therapeutic strategies, particularly for resistant cancers, by offering enhanced precision, reduced radiation doses, and improved therapeutic outcomes. This review provides an overview of synchrotron radiation beamline characteristics, recent breakthroughs in imaging and radiotherapy, and their emerging applications in treating heart, breast, lung, bone, and brain conditions.